2007
DOI: 10.1021/la0634701
|View full text |Cite
|
Sign up to set email alerts
|

Stability and State of Aggregation of Aqueous Fibrinogen and Dipalmitoylphosphatidylcholine Lipid Vesicles

Abstract: The stability and state of aggregation of aqueous fibrinogen (FB) and dipalmitoylphosphatidylcholine (DPPC) vesicles in water or buffer at 25 degrees C were studied with dynamic light scattering (DLS), UV-vis spectroturbidimetry (ST), and cryo-transmission electron microscopy (cryo-TEM). In water, when 1000 ppm (0.10 wt %) DPPC dispersions were prepared with a protocol including extensive sonication, they contained mostly vesicles and were quite clear, transparent, and stable for at least 30 days. FB mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…(7). technique, provided evidence that mostly vesicles are present in such dispersions [9,10]. The images here show that the diameters of the vesicles ranged from 20 to 100 nm when observed 12 h after the dispersions were prepared, or from 30 to 200 nm 50 days later.…”
Section: Dls and Tem Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…(7). technique, provided evidence that mostly vesicles are present in such dispersions [9,10]. The images here show that the diameters of the vesicles ranged from 20 to 100 nm when observed 12 h after the dispersions were prepared, or from 30 to 200 nm 50 days later.…”
Section: Dls and Tem Resultsmentioning
confidence: 50%
“…This preparation protocol method was originally described in Refs. [6][7][8][9][10] and is designed to produce dispersions containing primarily fluid vesicles (unilamellar particles). The effect of sonication time was also examined.…”
Section: Dispersion Preparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many examples of such interactions are known; for example, lactoferrin (36), protein C (37), and myeloperoxidase (38) interact with CERU; at least 11 proteins are known to interact with FGN including vitronectin (39), histidine-rich glycoprotein (40), and apolipoprotein(a) (41); and over 60 different proteins are believed to interact with HSA (42). Self-aggregation, which has been reported for both FGN (43) and HSA (44), may also account for the detection of these proteins as larger species. Corresponding analyses of stressed plasma strongly detected CLU and each of the three client proteins CERU, FGN, and HSA in fractions representing still larger species approaching (or at) the exclusion limit of the SEC column (4 ϫ 10 7 Da; Fig.…”
Section: Discussionmentioning
confidence: 73%
“…[24] In this work we report R H ¼ 252 Å for c Fbg ¼ 0.5 wt.-% (D ¼ 0). It is possible that our results are affected by c Fbg , since it has been shown that R H increases with c Fbg , [25] probably due to glycoprotein aggregation.…”
Section: Resultsmentioning
confidence: 62%